Vancouver School of Art : The Early Years, 1925-1939 : The inaugural exhibition of the Charles H. Scott Gallery. - Emily Carr College of Art, Granville Island, Vancouver (Vancouver : Charles H. Scott Gallery, 1980)
Amess, Fred ; Lamb Bobak, Molly ; Hughes, E.J. ; Lennie, Beatrice ; Weston, W.P. ; Macdonald, J.W.G. ; Goranson, Paul ; Rand, Paul ; Weatherbie, Vera ; Scott, Charles H. ; Varley, Frederick H. ; etc.
Vancouver School of Art : The Early Years, 1925-1939 : The inaugural exhibition of the Charles H. Scott Gallery, Emily Carr College of Art, Granville Island, Vancouver, 15 September to 15 October, 1980
English
kunstcatalogus